2021
DOI: 10.3390/ani11082411
|View full text |Cite
|
Sign up to set email alerts
|

Shade Modifies Behavioral and Physiological Responses of Low to Medium Production Dairy Cows at Pasture in an Integrated Crop-Livestock-Forest System

Abstract: Under conditions of high temperature, humidity, and incidence of solar radiation, dairy cows use behavioral changes as a strategy to decrease the metabolic heat production at pasture. The objective of this study was to evaluate the behavioral and physiological responses of Gyr and Girolando (5/8 Holstein 3/8 Gyr, and ½ Holstein ½ Gyr) dairy cows submitted to environments with and without shade. The experiment was conducted at Embrapa Cerrados (Technology Center for Dairy Zebu breeds—CTZL), Brasilia, Distrito F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It is known that milk yield of high-producing dairy cows will reduce when the minimum THI of a day exceeds 65 units (Zimbelman et al, 2009). In this study, we used the value of 74 of THI as a threshold to determine the thermal comfort (Reis et al, 2021), due to the cows`features (primiparous Zebu) of this study, and we did not find an effect of THI on milk yield. The cows in this study showed a lactation peak in the third month, then maintained their milk yield until the 6th month and reduced from the 7th month onwards.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that milk yield of high-producing dairy cows will reduce when the minimum THI of a day exceeds 65 units (Zimbelman et al, 2009). In this study, we used the value of 74 of THI as a threshold to determine the thermal comfort (Reis et al, 2021), due to the cows`features (primiparous Zebu) of this study, and we did not find an effect of THI on milk yield. The cows in this study showed a lactation peak in the third month, then maintained their milk yield until the 6th month and reduced from the 7th month onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, this is due to the supply of supplementation and the strategies adopted by the animals to overcome situations of intense heat or rain ( 45 ). Immediately after the offer, the animals start feed intake, and, in reflex, the rumination activity is also influenced since it occurs soon after ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Several advantages have been documented concerning the adoption of SPS in comparison to extensive grazing systems based on forage monocultures, emerging as a promising strategy to mitigate the environmental impact of livestock farming and enhance the resilience of tropical pasture systems towards climate uctuations. These bene ts include improvements in soil physical, chemical, and biological properties (Santos et al 2022), soil organic carbon storage (Resende et al 2020; Filho et al 2024), as well as similar total forage accumulation and greater nutritive value (Gomes et al 2022;Brunetti et al 2022), protein supply during the dry season (Ovani et al 2023), weed reduction (Munaro et al 2023), shaded pasture for animals (Reis et al 2021), promotion of animal welfare (Cândido et al 2023), improved animal performance (Oliveira et al 2022), greenhouse gas emission mitigation (Monteiro et al 2024) and, consequently, provision of ecosystem services (Schmitt Filho et al 2023). These bene ts depend on the characteristics or application of each chosen tree or shrub resource.…”
Section: Introductionmentioning
confidence: 99%